Violence and sorority developed in the Andean context of “Sangre coagulada”, by Mónica Ojeda - Herrera Mendoza, Camila Alexandra (2023)
The present investigation focuses on the development of the theme of violence directed towards the female gender and on the sorority that unfolds in the Andean context embodied in the story “Sangre coagulada” from the book Las voladoras (2020) by Mónica Ojeda. The attention is especially focused on the character of the “grandmother” from an Andean Gothic perspective, because she is presented as a violated and socially marginalized figure who, at the same time, represents the sorority that counteracts violence against women. Due to her work as an abortionist, she and her granddaughter are pointed out by the town’s inhabitants as abject subjects, because they transgress the social and moral order of the town. This makes her a “witch” of the community. Therefore, to support the topic of study on violence against women and sorority, the theoretical contributions of bell hooks, Walter Benjamin and Judith Butler, among others, will be used. Then, the analysis is carried out, which is divided into two sections: violence in female characters and sisterhood in the face of violence against women. Finally, the conclusions obtained are presented.